2016
DOI: 10.1111/jce.12910
|View full text |Cite
|
Sign up to set email alerts
|

Catheter Ablation of Ischemic Ventricular Tachycardia With Remote Magnetic Navigation: STOP‐VT Multicenter Trial

Abstract: Conclusions: This first prospective, single-procedure, multicenter study indicates that remote magnetic navigation is a safe and effective method for catheter ablation of post

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…Our experience regarding the feasibility of ventricular mapping using the novel basket catheter and related underlying annotation algorithms is in line with the recently published first case series on this new mapping catheter and system . The acquired mapping points in the present study exceed the usual amount gained by established 3‐D mapping systems by far and information on the underlying morphological and functional substrate could be obtained simultaneously. Compared to our experience, mapping time during sinus or paced rhythm is not faster than established 3‐D mapping systems despite using the multielectrode basket catheter, but, importantly, results in high spatial resolution of voltage maps and reliable isochronal maps with minimized inaccuracies from interpolation.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our experience regarding the feasibility of ventricular mapping using the novel basket catheter and related underlying annotation algorithms is in line with the recently published first case series on this new mapping catheter and system . The acquired mapping points in the present study exceed the usual amount gained by established 3‐D mapping systems by far and information on the underlying morphological and functional substrate could be obtained simultaneously. Compared to our experience, mapping time during sinus or paced rhythm is not faster than established 3‐D mapping systems despite using the multielectrode basket catheter, but, importantly, results in high spatial resolution of voltage maps and reliable isochronal maps with minimized inaccuracies from interpolation.…”
Section: Discussionsupporting
confidence: 84%
“…The induced VT was defined as the clinical VT, when cycle length (CL, within 20 miliseconds) and morphology matched previous recordings (12-lead ECG and/or device recordings). If a 12-lead ECG of the presenting VT was not available before ablation, induced VT similar in rate and intracardiac electrogram pattern to a spontaneous VT detected by an ICD were designated presumptive clinical VT. 2,11,12 Hemodynamic instability was defined as mean arterial blood pressure below 50 mmHg (invasive measurement). A catheter in the coronary sinus (CS) served as the reference for the Rhythmia TM 3-D electro-anatomical mapping system (Boston Scientific) in most cases.…”
Section: Electrophysiological Evaluation and Instrumentationmentioning
confidence: 99%
“…Studies examining outcomes using RMN for catheter ablation of ventricular arrhythmias (VAs) are summarized in Table 2. Several retrospective and prospective observational studies of ablation of scar‐associated ventricular tachycardia (VT) have shown that RMN‐guided ablation is associated with lower fluoroscopy times, comparable procedure times and comparable success rates when compared to manual ablation 27,29,30 …”
Section: Outcomes With Robotic‐assisted Catheter Ablationmentioning
confidence: 99%
“…21 guided ablation is associated with lower fluoroscopy times, comparable procedure times and comparable success rates when compared to manual ablation. 27,29,30 However, all of these studies are limited by its observational design, which introduces selection bias into the analyses. The ongoing prospective randomized controlled MAG-NETIC VT trigal is enrolling subjects with ischemic VT and severe left ventricular dysfunction and randomizing them to treatment with RMN-guided versus manual ablation with the primary study endpoint being 1-year freedom from VT. 35 Several retrospective observational studies have identified either improved or comparable success rates for ablation of idiopathic ventricular arrhythmias (VAs) using RMN-guided ablation when compared to manual ablation.…”
Section: Amigo Remote Catheter Systemmentioning
confidence: 99%
“… 35 Prospective data on treatment using the robotic technique are beginning to be validated in the treatment of ventricular tachycardia. 38 – 40 A recent study has compared the manual (n=80) and robotic methods and has shown the robotic method to be superior in the treatment of ischemic ventricular tachycardia over a follow-up period of 15 months, with a recurrence rate of 41% versus 19%, respectively. 37 While the results appear to be similar in other indications, such as dilated cardiomyopathy or dysplasia, the utility of RMNS in the epicardial approach is widely reported in the international literature.…”
Section: Clinical Trials With Rmns (Stereotaxis)mentioning
confidence: 99%